HISTORY OF MODERN FRENCH LITERATURE - Тоирова Дилфуза Файзуллаевна (American Journals Publishing, 2023)
The article discusses the social novel of the 70s, which combine various modern artistic trends and styles. Today's acute problems unite authors of different political and philosophical views, including writers related to Catholicism.
Keywords: Politics, society, people, students, movement, history, literature, resistance, culture, etc.